2017
DOI: 10.2147/dddt.s130514
|View full text |Cite
|
Sign up to set email alerts
|

Proteinopathy, oxidative stress and mitochondrial dysfunction: cross talk in Alzheimer's disease and Parkinson's disease

Abstract: Alzheimer’s disease and Parkinson’s disease are two common neurodegenerative diseases of the elderly people that have devastating effects in terms of morbidity and mortality. The predominant form of the disease in either case is sporadic with uncertain etiology. The clinical features of Parkinson’s disease are primarily motor deficits, while the patients of Alzheimer’s disease present with dementia and cognitive impairment. Though neuronal death is a common element in both the disorders, the postmortem histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
195
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(202 citation statements)
references
References 152 publications
(278 reference statements)
6
195
0
1
Order By: Relevance
“…As it is expected, ICS II mitigated Aβ-induced neuronal death through inhibiting PDE5 and regulating Caspase 3, consistent with previous findings in vivo [5]. Furthermore, several studies revealed that oxidative stress is the redox state resulting from an imbalance between the generation and detoxification of ROS, and it is known to play an important role in the [30]. Aggravation of Aβ promotes ROS overproduction and excessive ROS accelerates the neurotoxicity of Aβ in turn [31].…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 89%
“…As it is expected, ICS II mitigated Aβ-induced neuronal death through inhibiting PDE5 and regulating Caspase 3, consistent with previous findings in vivo [5]. Furthermore, several studies revealed that oxidative stress is the redox state resulting from an imbalance between the generation and detoxification of ROS, and it is known to play an important role in the [30]. Aggravation of Aβ promotes ROS overproduction and excessive ROS accelerates the neurotoxicity of Aβ in turn [31].…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 89%
“…This senescent phenotype seems to depend on the mitochondrial accumulation of proteasomal client substrates. Thus, mitochondrial accumulation of unfolded proteins, rather than MAPA formation, is probably responsible for the occurrence of cell senescence, in agreement with the fact that even monomeric aggregation-prone proteins are toxic to mitochondria and cells (Ganguly et al, 2017). The effects of these molecules on cell senescence were highly correlated with their effects on the mitochondrial accumulation of proteasomal clients.…”
Section: Fundc1 and Hsc70 Are Required For The Proteotoxic Stressindusupporting
confidence: 66%
“…All these supported that attenuated AMPK activation and impaired insulin signaling may act as a detecting factor representing an underlying mechanism of αSyn pathology. On the other hand, evidence suggesting that oxidative stress elicited by mitochondrial dysfunction may be involved in the process of αSyn‐induced neurotoxicity . Particularly, in vitro studies have shown that increasing levels of oxidative stress can lead to αSyn aggregation .…”
Section: Discussionmentioning
confidence: 99%